The Effect of Third Party Funds, Return on Assets, Loan to Deposit Ratio, Capital Adequacy Ratio, Operating Expenses and Operating Income on Credit Distribution in Banking Companies Listed on the Indonesia Stock Exchange - Aritonang, Lamria; Katharina, Ninta; Siringo-Ringo, Eko Deswin Miecaels (International Journal of Education, Management, and Technology, 2025)
This study aims to determine whether third party funds, return on assets, loan to deposit ratio, capital adequacy ratio and operating expenses of operating income affect the distribution of banking credit. This study is a quantitative study. Sampling was carried out using purposive sampling, therefore there are 26 banking companies included in this category. The hypothesis of this study was tested using multiple linear regression. The results of the study describe various results. The conclusion of the study is that third party funds have an influence on the distribution of banking credit and are not significant while return on assets, loan to deposit ratio, capital adequacy ratio, and operating expenses of operating income do not have an influence and are significant on the distribution of company credit.